Caught off guard and beaten: The Ukraine war and food security in the Middle East - Al-Saidi, Mohammad (Frontiers in Nutrition, 2023)
The Ukraine war has led to a severe global food crisis due to complex supply disruptions and price increases of agricultural inputs. Countries of the Middle East have been directly affected because of their high dependence on food imports from Russia and Ukraine. Furthermore, this food crisis comes at times of high baseline vulnerability due to the compound impacts of COVID-19, repeated food shocks, and weakened states due to political-economic difficulties. This paper provides a detailed analysis of the food-related vulnerability of Middle Eastern countries in the wake of the Ukraine war. It contextualizes the varying impacts of this crisis in the region, and highlights country-level response strategies. The analysis shows a concerning and deepened crisis in the case of highly exposed and politically fragile countries with weakened food sectors; e.g., Lebanon, Sudan, and Yemen. Political economic instabilities, limited domestic agriculture, and the lack of reliable grain reserves have aggravated the current food crisis in some countries. At the same time, indigenous short-term responses related to regional aid and cooperation have emerged, particularly in the Gulf countries, which have witnessed soaring revenues from higher energy prices. Alongside more regional frameworks for collaboration on food security, future action to mitigate such food crises should include the strengthening of local sustainable agriculture, storage capacities, and grain procurement strategies from international suppliers.